2021
DOI: 10.1126/sciadv.abg6600
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-specific KLF4 is required to maintain parietal epithelial cell quiescence in the kidney

Abstract: Podocyte loss triggering aberrant activation and proliferation of parietal epithelial cells (PECs) is a central pathogenic event in proliferative glomerulopathies. Podocyte-specific Krüppel-like factor 4 (KLF4), a zinc-finger transcription factor, is essential for maintaining podocyte homeostasis and PEC quiescence. Using mice with podocyte-specific knockdown of Klf4, we conducted glomerular RNA-sequencing, tandem mass spectrometry, and single-nucleus RNA-sequencing to identify cell-specific transcriptional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Lineage tracing by genetic tagging employing both podocyte and PEC-specific reporter mice in a model mimicking CG finally proved that hyperplastic cells were not podocyte-derived, but of PEC origin ( Suzuki et al, 2009 ). Moreover, a recent multiomics study reported that podocyte-specific knockdown of Krüppel-like factor 4 contributes to podocyte loss triggering the activation of a distinct PEC subpopulation, suggesting that in this disorder PEC proliferation and pseudocrescent formation represent a response to podocyte injury and loss ( Pace et al, 2021 ).…”
Section: Collapsing Glomerulopathymentioning
confidence: 99%
“…Lineage tracing by genetic tagging employing both podocyte and PEC-specific reporter mice in a model mimicking CG finally proved that hyperplastic cells were not podocyte-derived, but of PEC origin ( Suzuki et al, 2009 ). Moreover, a recent multiomics study reported that podocyte-specific knockdown of Krüppel-like factor 4 contributes to podocyte loss triggering the activation of a distinct PEC subpopulation, suggesting that in this disorder PEC proliferation and pseudocrescent formation represent a response to podocyte injury and loss ( Pace et al, 2021 ).…”
Section: Collapsing Glomerulopathymentioning
confidence: 99%
“…The majority of pluripotent markers in iPSC-derived podocytes showed low to no mRNA expression. Two exceptions were PODXL and KLF4 that both showed clear expression that remained consistent across all coating in the podocyte-like cells, this is expected as both genes play important roles in the formation and function of podocytes (Refaeli et al, 2020, Pace et al, 2021. Interestingly, KLF4, one of the Yamanaka factors used for the reprogramming of iPSCs (Takahashi and Yamanaka, 2006), showed a much higher difference in mRNA expression levels in undifferentiated iPSC, with a significantly greater expression for all three cell lines when cultured on fibroblast-ECM compared to any of the other coatings, including Geltrex (Figure 4).…”
Section: Ipsc Characterizationmentioning
confidence: 87%
“…By using RNA-sequencing, mass spectrometry, and single-cell RNA-sequencing, Pace et al have identified key ligand-receptor interactions between podocytes and PECs via KLF4/STAT3 signaling. Restoration of KLF4 expression in podocytes or inhibition of STAT3 signaling prevented the loss of podocytes and suppressed PEC activation in mice ( Pace et al, 2021 ).…”
Section: Parietal Epithelial Cells In Podocytopathymentioning
confidence: 99%